Specific features of regulatory T cells in patients with systemic lupus erythematosus - A. V. Torgashina; S. К. Solovyev (Современная ревматология, 2018)
Regulatory T cells (Tregs) is a CD4+ lymphocyte subpopulation that maintains autotolerance by suppressing the activity of autoreactive lymphocytes. There is a hypothesis that functional defects or a smaller number of Tregs underlie the pathogenesis of a number of autoimmune diseases. The paper considers the main features of the phenotype of Tregs. It discusses the number of Tregs in both peripheral blood and affected organs in systemic lupus erythematosus, as well as the time course of changes in the level and functional abilities of different subpopulations of Tregs during immunosuppressive therapy. In addition, the paper presents various approaches to using Treg lymphocytes in the therapy of autoimmune diseases.